Is the Impostor Phenomenon expressed in language? An LIWC analysis of textual self-descriptions - Brauer, Kay; Proyer, René T. (Frontiers in Psychology, 2025)
The Impostor Phenomenon (IP) describes individual differences in self-perceptions of intellectual fraudulence. Based on the notion that personality traits are reflected in individual differences in language use, the literature provided initial evidence that the IP relates to language use. While earlier research was limited to job application letters, we expanded the study of the interconnectedness between the IP and language use by analyzing open self-descriptions (length limited to up to five sentences). We analyzed short textual self-descriptions by 325 participants with Linguistic Inquiry and Word Count (LIWC) software and examined their associations with self-reports of the IP. Contrary to earlier research, we found that the IP is unrelated to language use according to quantitative text analysis with the LIWC, except for using more words expressing anxiety (r = 0.22). Thus, our findings show that the IP is not robustly connected to language use in the domain of broad textual self-descriptions. We discuss implications for the interpersonal perception of the IP and discuss future directions to extend this line of research.